Influence of source-to-collimator distance on image quality in single photon emission computed tomography: a phantom study - Sayed, Inayatullah Shah; Yusup, Nur Amirah (Kulliyyah of Allied Health Sciences, IIUM, 2020)
Introduction: Source-to-collimator distance is one of the physical factors that can affect the quality of images generated in Single Photon Emission Computed Tomography (SPECT). Therefore, this work investigated the effect of source-to-collimator distance on image quality in terms of uniformity, hot and cold regions contrast and signal-to-noise ratio (SNR). Methods: SPECT data were acquired by scanning R.A. Carlson’s cylindrical phantom using Philips ADAC Forte dual head gamma camera with parallel- hole low energy high resolution (LEHR) collimator. Five different settings of collimator to phantom distance were applied which were 26, 27, 28, 29 and 30cm. Reconstruction of the images was done by using filtered back-projection (FBP) in conjunction with Butterworth filter with cut off frequency of 0.35 cycle/cm and order 5. The reconstructed images were evaluated quantitatively via standard deviation, contrast and SNR. Results: It was found from the quantitative analysis that the standard deviation in the counts of uniform regions increased whereas the contrast and SNR of most hot and cold regions decreased with the increase in phantom-to-collimator distance. Conclusion: The farther the object to be imaged from the gamma camera collimator results, the poorer image quality of the reconstructed image. Therefore, in SPECT clinical examinations attention on the source-to-collimator distance needs to be given in order to achieve the diagnostic quality images.